Hubungan Budaya Organisasi Dengan Kinerja Pegawai Pada Kantor Sekretariat Daerah Kabupaten Bulukumba - Firnawati, Reski; Hakim, Lukman; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2020)
This study purposed to determine the Relationship between Organizational Culture and Employee Performance at the Regional Secretariat Office of Bulukumba Regency. This type of research was a survey research that illustrated quantitative analysis. Data collection techniques used questionnaires and documentation. The data was analyzed descriptively and quantitatively by using SPSS application. The population were 164 and the sample were 49. The sampling technique used random sampling techniques. The results of this study showed that there was a relationship between organizational culture and employee performance, with a correlation coefficient value = 0,671. This figure showed a strong correlation or relationship between Organizational Culture and Employee Performance of 67,1% and influenced by factors that existed in the employees themselves.